2009
DOI: 10.3921/joptom.2009.29
|View full text |Cite
|
Sign up to set email alerts
|

Do Peripheral Refraction and Aberration Profiles Vary with the Type of Myopia? - An Illustration Using a Ray-Tracing Approach

Abstract: Myopia is considered to be the most common refractive error occurring in children and young adults, around the world. Motivated to elucidate how the process of emmetropization is disrupted, potentially causing myopia and its progression, researchers have shown great interest in peripheral refraction. This study assessed the effect of the myopia type, either refractive or axial, on peripheral refraction and aberration profiles. METHODS: Using customized schematic eye models for myopia in a ray tracing algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…[12][13][14] Bakaraju et al have suggested that the risk for myopia progression could be higher in axial myopias compared to refractive ones according to their peripheral refractive pattern. 15 Interestingly, pioneer work from Cho and coauthors found a positive and statistically significant correlation between baseline spherical equivalent refraction and vitreous chamber depth elongation in the orthokeratology group such that the higher the baseline myopia the lower the myopic progression. Conversely, the opposite was found in the control group of spectacle wearers.…”
Section: Introductionmentioning
confidence: 96%
“…[12][13][14] Bakaraju et al have suggested that the risk for myopia progression could be higher in axial myopias compared to refractive ones according to their peripheral refractive pattern. 15 Interestingly, pioneer work from Cho and coauthors found a positive and statistically significant correlation between baseline spherical equivalent refraction and vitreous chamber depth elongation in the orthokeratology group such that the higher the baseline myopia the lower the myopic progression. Conversely, the opposite was found in the control group of spectacle wearers.…”
Section: Introductionmentioning
confidence: 96%
“…While defocus and astigmatism (lower-order aberrations) can be corrected with conventional spectacles or contact lenses, other optical imperfections described as higher-order aberrations (HOAs) cannot be corrected using traditional optical corrections and have the potential to alter retinal image quality 12 , 13 which may provide cues to the retina 14 , and possibly lead to the development of myopia 15 . Numerous studies have investigated the relationships between HOAs and age 16 21 , axial length 22 , 23 , refractive error 24 , accommodation 13 , 25 , and ethnicity 24 , 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Bakaraju et al have suggested that the risk for myopia progression could be higher in axial myopias compared to refractive ones according to their peripheral refractive pattern. 17 Despite these findings, the characterization of peripheral refraction after corneal reshaping has only been addressed by a limited number of studies. 18 In the work of Charman et al, the authors showed for the first time the actual changes in off-axis refraction induced by ortho-k treatment.…”
Section: Introductionmentioning
confidence: 99%